Psycholinguistics Study on Students with Lisp Disorders in SMPIT Nurul Qolbi Bekasi - Khotimah, Husnul; Zainal Rafli; Fathiaty Murtadho (Universitas Cokroaminoto Palopo, 2025)
One of the speech disorders in adolescence to adulthood is lisping, which is a speech impairment where there is difficulty in pronouncing the /r/ phoneme. A lisp involves an assimilation of sound changes that are imperfect when pronouncing the /r/ phoneme. This study aims to explore that communication with individuals who have a lisp is quite different compared to communication with individuals without speech disorders. The focus of this research is on adolescent lisp sufferers. The research method used is qualitative descriptive. The data collection techniques used in this study are recording, observation, and note-taking. Afterward, the data will be transcribed. The data sources are the students of SMPIT Nurul Qolbi on the consonants /r/ and /s/. The data consists of utterances from two informants. The results of this study show that Syafa Azzahra obtained 28 data points on the lisp disorder “S” and Ananda Rizky Ramadhan obtained 19 data points on the /r/ phoneme.